Resentment against Racism in Koirala’s Sumnima - Shrivastwa, Bimal Kishore (Journal of Language and Literature, 2024)
The present paper seeks to analyze resentment against racism and ethnic consciousness in Bishweshwar Prasad Koirala’s novel, Sumnima, from the theoretical perspectives of race and ethnicity advocated by mainly by Thomas Hylland Eriksen. This paper explores how the novel primarily delineates the conflict between the Aryans, the so-called hegemonic group, and non-Aryans, particularly Kirats and Bhillas, the subjugated marginal community, in the Nepalese society. The obvious reason for conflict is cultural or religious differences. The dominant Aryansin the novel think themselves superior to Kirats and Bhillas. They think that they are the civilized ones as they obtain divinity through hard penance and spiritual transformation, while non-Aryans are wild, uncivilized, and devoid of good culture. It is expected that the research will be a useful reference for the researchers intending to probe into the Nepalese literature from the perspective of cultural studies.